(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
Alain (Émile Chartier), 1920: Système des beaux-arts, Paris, Gallimard, 1920. Burdea, G.C., Coiffet P., 1993: Virtual Reality Technology, Hoboken, New Jersey, John Wiley & Sons Inc., 2003. Dufrenne M., 1953: Phenomenology of aesthetic experience, by E. Casey, Northwestern University Press, Evanston, 1973. Dufrenne M., 1963: Le poétique, Paris, P.U.F., 1963. Dufrenne M., 1966: Jalons, Nijhoff, La Haye, 1963. Dufrenne M., 1967: Esthétique et Philosophie, vol. I, Paris, Klincksieck, 1967. Dufrenne M., 1976a: Esthétique et Philosophie, vol. II, Paris, Klincksieck, 1967. Dufrenne M., 1981a: L’inventaire des a priori: recherche de l’originaire, Paris, Bourgois, 1981. Dufrenne M., 1981b: Esthétique et Philosophie, vol. III, Klincksieck, Paris. 1981. Dufrenne M., 1987: L’oeil et l’oreille, Montreal, L’HEXAGONE, 1987. Franzini E., 1982: Natura e Poesia, Su un inventario degli a priori di Mikel Dufrenne, in Fenomenologia e scienze dell’uomo, Padova, CLESP editrice, pp. 67-90. Sartre J.P., 1940: The psychology of imagination, New York, Philosophical library, 1948.